Therapeutic Potential of Herbal Medicines in Combating Particulate Matter (PM)-Induced Health Effects: Insights from Recent Studies - Aekkhaluck Intharuksa; Warunya Arunotayanun; Mingkwan Na Takuathung; Yaowatat Boongla; Siripat Chaichit; Suthiwat Khamnuan; Anchalee Prasansuklab (Antioxidants)
Particulate matter (PM), particularly fine (PM2.5) and ultrafine (PM0.1) particles, originates from both natural and anthropogenic sources, such as biomass burning and vehicle emissions. These particles contain harmful compounds that pose significant health risks. Upon inhalation, ingestion, or dermal contact, PM can penetrate biological systems, inducing oxidative stress, inflammation, and DNA damage, which contribute to a range of health complications. This review comprehensively examines the protective potential of natural products against PM-induced health issues across various physiological systems, including the respiratory, cardiovascular, skin, neurological, gastrointestinal, and ocular systems. It provides valuable insights into the health risks associated with PM exposure and highlights the therapeutic promise of herbal medicines by focusing on the natural products that have demonstrated protective properties in both in vitro and in vivo PM2.5-induced models. Numerous herbal medicines and phytochemicals have shown efficacy in mitigating PM-induced cellular damage through their ability to counteract oxidative stress, suppress pro-inflammatory responses, and enhance cellular defense mechanisms. These combined actions collectively protect tissues from PM-related damage and dysfunction. This review establishes a foundation for future research and the development of effective interventions to combat PM-related health issues. However, further studies, including in vivo and clinical trials, are essential to evaluate the safety, optimal dosages, and long-term effectiveness of herbal treatments for patients under chronic PM exposure.